2003
DOI: 10.1099/mic.0.26153-0
|View full text |Cite
|
Sign up to set email alerts
|

Lic16A of Clostridium thermocellum, a non-cellulosomal, highly complex endo-β-1,3-glucanase bound to the outer cell surface

Abstract: Clostridium thermocellum produces one major b-1,3-glucanase. Genomic DNA fragments containing the gene were cloned from two strains, DSM1237T (6848 bp) and F7 (9766 bp).Overlapping sequences were 99?9 % identical. The nucleotide sequences contained reading frames for a putative transposase, endo-b-1,3-1,4-glucanase CelC, a putative transcription regulator of the LacI type, b-1,3-glucanase Lic16A and a putative membrane protein. The licA genes of both strains encoded an identical protein of 1324 aa with a calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 57 publications
5
32
0
Order By: Relevance
“…However, the binding stoichiometry ratios for glucose and cellobiose were higher than 1 (1.8 and 2.2, respectively). Since CbpC mocellum can also grow on laminarin (␤-1,3 glucan) as a sole carbon source (15), consistent with the presence of the observed laminaribiose transport system. Recently, laminaribiose was found to be the molecular inducer of the celC operon in C. thermocellum (22), which is composed of three genes, namely, celC (endo-␤-1,4-glucanase), licA [endo-␤-1,3(4)-glucanase], and glyR3 (celC operon repressor).…”
Section: Resultssupporting
confidence: 54%
“…However, the binding stoichiometry ratios for glucose and cellobiose were higher than 1 (1.8 and 2.2, respectively). Since CbpC mocellum can also grow on laminarin (␤-1,3 glucan) as a sole carbon source (15), consistent with the presence of the observed laminaribiose transport system. Recently, laminaribiose was found to be the molecular inducer of the celC operon in C. thermocellum (22), which is composed of three genes, namely, celC (endo-␤-1,4-glucanase), licA [endo-␤-1,3(4)-glucanase], and glyR3 (celC operon repressor).…”
Section: Resultssupporting
confidence: 54%
“…It was discussed as a possible cause for the "module shuffling" expected for cellulosomal genes and has been proposed to be the source of their modular composition. Multiple copies of this putative IS element were identified in the genome (10). However, no obvious connection between the locations of the cellulosomal genes and those of the IS1447 elements was found (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Another gene cluster consists of the genes encoding the noncellulosomal endoglucanase CelC, a LacI-like protein, the lichenan-degrading enzyme LicA, and a potential membrane protein with eight putative transmembrane regions (86). We (246) reported that this gene cluster is immediately upstream of the genes encoding ManB (171) and CelT (172).…”
Section: Cellulase Gene Clustersmentioning
confidence: 99%
“…It contains no dockerin domain but does have SLH segments (32). Similarly, LicA contains three SLH domains at its N-terminal end that have been shown to mediate its association with cells (86). Many scaffoldins, including that of C. cellulovorans (CbpA), do not have a dockerin.…”
Section: Attachment Of Cellulosomes To the Cell Surfacementioning
confidence: 99%
See 1 more Smart Citation